2013
DOI: 10.1002/hep.26585
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic myofibroblasts promote the progression of human cholangiocarcinoma through activation of epidermal growth factor receptor

Abstract: Intrahepatic cholangiocarcinoma (CCA) is characterized by an abundant desmoplastic environment. Poor prognosis of CCA has been associated with the presence of alpha‐smooth muscle actin (α‐SMA)‐positive myofibroblasts (MFs) in the stroma and with the sustained activation of the epidermal growth factor receptor (EGFR) in tumor cells. Among EGFR ligands, heparin‐binding epidermal growth factor (HB‐EGF) has emerged as a paracrine factor that contributes to intercellular communications between MFs and tumor cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 45 publications
4
87
0
Order By: Relevance
“…CAFs have a crucial role in favoring CCA progression, and more particularly in promoting EMT, through interactive autocrine and paracrine signaling pathways [68,131]. We have recently shown that CAFs from human iCCA synthesize HB-EGF, which activates EGFR in CCA cells leading to the disruption of cell-cell junctions and an increase of invasiveness [68]. Furthermore, we described a paracrine reciprocal loop in which CCA cells produced TGF-β1 that stimulates HB-EGF expression by CAF.…”
Section: Cancer-associated Fibroblasts (Cafs) and Hepatic Stellate Cementioning
confidence: 91%
See 3 more Smart Citations
“…CAFs have a crucial role in favoring CCA progression, and more particularly in promoting EMT, through interactive autocrine and paracrine signaling pathways [68,131]. We have recently shown that CAFs from human iCCA synthesize HB-EGF, which activates EGFR in CCA cells leading to the disruption of cell-cell junctions and an increase of invasiveness [68]. Furthermore, we described a paracrine reciprocal loop in which CCA cells produced TGF-β1 that stimulates HB-EGF expression by CAF.…”
Section: Cancer-associated Fibroblasts (Cafs) and Hepatic Stellate Cementioning
confidence: 91%
“…TGF-β1-3 and their receptors TGF-β RI and RII were found expressed in both CCA tumor cells and surrounding stroma cells [65][66][67][68][69][70] while no data on TGF-β RIII expression is available. Regarding TGF-β1, it is expressed not only by invading malignant cholangiocytes, but also by stroma cells (e.g.…”
Section: Transforming-growth Factor-β (Tgf-β)-dependent Signaling Is mentioning
confidence: 99%
See 2 more Smart Citations
“…CAFs, which express α-smooth muscle actin, are able to modulate several processes (that is, prolifer ation, migration, invasion and EMT) in CCA tumour cells 139,[175][176][177][178][179][180] . Accordingly, patients with high levels of α-smooth muscle actin expression in CCA tissue samples exhibit worse prognosis 181,182 .…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%